Pemahaman Muslim Berlangganan Restoran Halal: Peran Logo Halal dan Sikap Konsumen di Kota Bogor - Andika Nuraga Budiman; Intan Tri Annisa (Lembaga Penelitian Universitas YARSI, 2019)
The purpose of this study is to investigate the perception of Muslim costumers who always subscribing Halal restaurant without any doubt whenever they find Halal logo in restaurant or without it. This research is already finished with supported of SPSS ver.23. 200 respondents were giving the contribution to make this research. The result shows that despite all the hypothesis testing were investigate significantly, the mediation of consumer’s attitude was significantly mediate them to subscribe Halal restaurant. Which is the Muslim of Bogor were keep the Islam rule as an obligation to always consume permissible food and beverage in guarantee Halal in restaurant.